Exploring the Multidimensional Model of Leadership through the lens of coaches: an examination of the relationship between personality, leader behaviors, and the coach-athlete relationship - Anderson, S. N.; Harenberg, S.; Nieto, M.; Vosloo, J. (International Sport Coaching Journal, 2025)
The Multidimensional Model of Leadership hypothesizes that leader personality characteristics impact leader behaviors, which in turn influence collective and individual outcomes. While the Multidimensional Model of Leadership has received substantial research attention over the past four decades, the full hypothesis including antecedents, throughputs, and outputs has rarely been tested in one study. Hence, the purpose of the present study was to test the relationship between adaptive and maladaptive personality characteristics (i.e., perfectionism and passion), leader behaviors, and the coach-athlete relationship in college coaches. National Collegiate Athletic Association coaches (N = 380) completed the Sport Multidimensional Perfectionism Scale-2, the Passion Scale, the Leadership Scale for Sports, and the Coach-Athlete Relationship Questionnaire. Structural equation modeling revealed that perfectionism and passion accounted for 65% of the variance for leader behaviors. Specifically, adaptive dimensions of perfectionism and passion positively predicted leader behaviors, whereas maladaptive dimensions of perfectionism negatively predicted leader behaviors. Furthermore, leader behaviors explained over half the variance of the coach-athlete relationship. The results provide support for the Multidimensional Model of Leadership from the perspective of sport coaches. Applied implications for coaches and sport psychology practitioners are discussed.